Erythropoietin as a neonatal neuroprotectant: basic and clinical studies (Hematology Meeting Reports, 2009)
Neonatal brain injury Although there are many mechanisms by which the neonatal brain can sustain injury, perinatal asphyxia and preterm delivery are two common mechanisms. To date, effective treatment strategies to improve neurodevelopmental outcome are not yet available. Perinatal asphyxia occurs in 2-4 of every 1000 live-born term infants,1 and accounts for 23% of neonatal deaths world wide.2 In recently published hypothermia trials, between 55 and 62% of infants diagnosed with perinatal asphyxia treated with conventional therapy died or survived with significant neurodevelopmental disability.3,4